2021
DOI: 10.3389/fcell.2021.659951
|View full text |Cite
|
Sign up to set email alerts
|

LAR Receptor Tyrosine Phosphatase Family in Healthy and Diseased Brain

Abstract: Protein phosphatases are major regulators of signal transduction and they are involved in key cellular mechanisms such as proliferation, differentiation, and cell survival. Here we focus on one class of protein phosphatases, the type IIA Receptor-type Protein Tyrosine Phosphatases (RPTPs), or LAR-RPTP subfamily. In the last decade, LAR-RPTPs have been demonstrated to have great importance in neurobiology, from neurodevelopment to brain disorders. In vertebrates, the LAR-RPTP subfamily is composed of three memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 178 publications
(346 reference statements)
3
37
0
Order By: Relevance
“…Nonfunctional PTPRD have been reported in other gliomas (Veeriah et al, 2009) and its loss was found to cause aberrant STAT3 activation promoting glioma (Ortiz et al, 2014). In adult brains PTPRD is involved in trans-synaptic interaction between neurons (Yoshida et al, 2011) and mediates cortical basal dendritic arborization, synaptic plasticity and neuronal growth in perineuronal nets (Carulli and Verhaagen, 2021; Cornejo et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Nonfunctional PTPRD have been reported in other gliomas (Veeriah et al, 2009) and its loss was found to cause aberrant STAT3 activation promoting glioma (Ortiz et al, 2014). In adult brains PTPRD is involved in trans-synaptic interaction between neurons (Yoshida et al, 2011) and mediates cortical basal dendritic arborization, synaptic plasticity and neuronal growth in perineuronal nets (Carulli and Verhaagen, 2021; Cornejo et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Expression patterns for the three genes are distinct but certainly display overlap and the same can be said about their ligand and substrate specificity. A thorough review with a specific focus on their role in the brain was published recently ( Cornejo et al, 2021 ). A decade ago, only limited evidence linking these three RPTP genes to hereditary diseases had been gathered ( Hendriks and Pulido, 2013 ).…”
Section: Documented Genetic Variabilitymentioning
confidence: 99%
“…Having come to know PTPRD as a prime suspect for a plethora of disease conditions it is rather contrasting to see the limited hereditary dangers that have been tied to gene PTPRS , at least for the time being. Again largely thanks to studies in mutant mouse models the protein encoded by PTPRS , RPTPσ, demonstrated important roles in development and function of the nervous system ( Cornejo et al, 2021 ), including the control of synaptic transmission ( Brown et al, 2020 ). Also, RPTPσ functionality turned out to be a two-edged sword in the fight against intestinal inflammatory processes ( Ohtake et al, 2018 ); the protein not only protects the permeability of the epithelial layer ( Murchie et al, 2014 ) but also keeps dendritic cells under control ( Bunin et al, 2015 ).…”
Section: Documented Genetic Variabilitymentioning
confidence: 99%
“…Synaptic adhesion molecules (SAMs) accumulate at pre-and postsynaptic sites, initiate synapse formation, and play an important role in regulating synaptic transmission and synaptic plasticity (Jang et al, 2017;Sudhof, 2018;Südhof, 2021;Yuzaki, 2018;Kim et al, 2021). The presynaptic SAMs are mostly present in excitatory and inhibitory synapses, like neurexins which are a family of SAMs involved in synapse formation and maturation, and leukocyte antigen-related (LAR)-type phosphotyrosine phosphatase receptors (PTPRs) (Sudhof, 2017;Cornejo et al, 2021;Fukai and Yoshida, 2021). In contrast, postsynaptic SAMs are more diverse as ligands for these presynaptic SAMs and are often specific for excitatory or inhibitory synapses.…”
Section: Synaptic Adhesion Molecules and Proteins Mediating Synapse F...mentioning
confidence: 99%